A prospective cohort study of immunogenicity of quadrivalent human papillomavirus vaccination among Alaska Native Children, Alaska, United States. Issue 42 (29th September 2020) - Bruce, Michael G.; Meites, Elissa; Bulkow, Lisa; Panicker, Gitika; Hurlburt, Debby; Lecy, Danielle; Thompson, Gail; Rudolph, Karen; Unger, Elizabeth R.; Hennessy, Thomas; Markowitz, Lauri E.
Abstract: Objective: In the United States, HPV vaccination is routinely recommended at age 11 or 12 years; the series can be started at age 9. We conducted a cohort study to assess long-term immunogenicity of quadrivalent HPV vaccine (4vHPV) in an American Indian/Alaska Native (AI/AN) Indigenous population. Methods: During 2011–2014, we enrolled AI/AN girls and boys aged 9–14 years, who were vaccinated with a 3-dose series of 4vHPV. Serum specimens were collected at five time points: immediately prior to doses 2 and 3, and at one month, one year, and two years after series completion. Antibody testing was performed using a multiplex virus-like-particle-IgG ELISA for 4vHPV types (HPV 6/11/16/18). Results: Among 477 children (405 girls/72 boys) completing the 3-dose series, median age at enrollment was 11.2 years. Of the 477, 72 (15%) were tested before dose 2 and 70 (15%) before dose 3. Following series completion, 435 (91%) were tested at one month, 382 (80%) at one year, and 351 (74%) at two years. All tested participants had detectable antibody to 4vHPV types at all time points measured. Geometric mean concentrations (GMCs) for 4vHPV types at one month and two years post-series completion were 269.9 and 32.7 AU/ml for HPV6, 349.3 and 42.9 AU/ml for HPV11, 1240.2 and 168.3 IU/ml HPV16, and 493.2 and 52.2 IU/ml for HPV18. Among children tested after each dose, GMCs after doses 1 and 2 were 3.9 and 32.2 AU/ml for HPV6, 5.3 and 45.6 AU/ml for HPV11, 20.8 and 187.9 IU/ml for HPV16; and 6.6 and 49.7 IU/ml for HPV18. No serious adverse events were reported. Conclusion: All AI/AN children developed antibodies to all 4vHPV types after vaccination. GMCs rose after each dose, then decreased to a plateau over the subsequent two years. This cohort will continue to be followed to determine duration of antibody response.